Processo do gerenciamento dos clientes a partir de canais digitais no segmento de veículos comerciais - Sousa, Bruno Rocha de (2024)
The objective of the work is to establish a management process that allows tracking of leads generated through digital channels available to customers who are interested in purchasing commercial vehicles. Based on the diagnosis of the influence of digital channels, a system for monitoring these interactions was defined, the process of tracking customer relationships through digital channels was established, and the viability of these communications using data obtained through CRM was analyzed. It was necessary to establish an automated process that guaranteed agility, assertiveness and security of information to ensure the traceability of customer relationships on digital channels in the commercial vehicle segment at a truck dealership. The results obtained were an increase in the number of vehicles sold, in 2022 it was an increase of 1200% compared to 2021, in 2023 even with the sector in decline in the market as a whole, there was an increase of 300% compared to 2021 and a drop of 80% in reaction to 2022.